2017
DOI: 10.1038/s41598-017-06640-y
|View full text |Cite
|
Sign up to set email alerts
|

The Frustration-induced Ferroelectricity of a Manganite Tricolor Superlattice with Artificially Broken Symmetry

Abstract: In this paper, [(La0.9Sr0.1MnO3)n/(Pa0.9Ca0.1MnO3)n/(La0.9Sb0.1MnO3)n]m superlattices films have been deposited on (001) Nb:SrTiO3 substrates by a laser molecular-beam epitaxy technology. Expected ferroelectricity arise at well-defined tricolor superlattice at low temperature, composed of transition metal manganite, which is absent in the single-phase compounds. Furthermore, the ferroelectric properties of the superlattices are enhanced by increasing the periodicity m, which may be attributed to the accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…To investigate the ferroelectric behavior of the sample, capacitance-voltage measurements were carried out at room temperature by varying the DC electric field from +5 V to −5 V at 1MHz applied frequency. A characteristic butterfly shaped Capacitance-Voltage loop ( Figure 11) was observed which indicated a ferroelectric polarization switching [35]. To investigate the ferroelectric behavior of the sample, capacitance-voltage measurements were carried out at room temperature by varying the DC electric field from +5 V to −5 V at 1MHz applied frequency.…”
Section: Impedance Fitting Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the ferroelectric behavior of the sample, capacitance-voltage measurements were carried out at room temperature by varying the DC electric field from +5 V to −5 V at 1MHz applied frequency. A characteristic butterfly shaped Capacitance-Voltage loop ( Figure 11) was observed which indicated a ferroelectric polarization switching [35]. To investigate the ferroelectric behavior of the sample, capacitance-voltage measurements were carried out at room temperature by varying the DC electric field from +5 V to −5 V at 1MHz applied frequency.…”
Section: Impedance Fitting Resultsmentioning
confidence: 99%
“…To investigate the ferroelectric behavior of the sample, capacitance-voltage measurements were carried out at room temperature by varying the DC electric field from +5 V to −5 V at 1MHz applied frequency. A characteristic butterfly shaped Capacitance-Voltage loop ( Figure 11) was observed which indicated a ferroelectric polarization switching [35].…”
Section: Impedance Fitting Resultsmentioning
confidence: 99%
“…In Ref. [65], it was shown that magnetic frustration results in a phase competition, which is the origin of the magnetoelectric response. A possible experimental realization of an isolated skyrmion as well as a skyrmion lattice has been suggested [66].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 65 it was shown that magnetic frustration results in a phase competition, which is the origin of the magnetoelectric response. A possible experimental realization of an isolated skyrmion as well as a skyrmion lattice has been suggested 66 .…”
Section: Introductionmentioning
confidence: 99%